Influence of Experiential Marketing on Patient Loyalty Through Patient Satisfaction as Intervening Variable - Hidayah, Alfina Okta Nur; Marsudi; Andharini, Sri Nastiti (Business Innovation Management and Entrepreneurship Journal, 2023)
This study aimed to analyze and describe the effect of experiential marketing, patient satisfaction, and patient loyalty at As-Syifa Husada Clinic. This research uses quantitative research. The population of this study is people who are currently or have used the services of the As-Syifa Husada Clinic, and the sample is 110 respondents who have used the services of the KIA Poly (Mother & Child Clinic) at least two times. Data collection techniques in this study used a questionnaire distributed to respondents. The analytical method used is path analysis and hypothesis testing using T-test and mediation test using the SPSS analysis tool. The results of this study indicate that: Experiential marketing has a positive and significant effect on patient loyalty; Experiential marketing has a positive and significant effect on patient satisfaction; Patient satisfaction has a positive and significant effect on patient loyalty; experiential marketing has an influence on patient loyalty through patient satisfaction. Good experiential marketing can shape patient satisfaction which will also have an impact on creating patient loyalty at As-Syifa Husada Clinic.